LEMBAGA MASYARAKAT PEDULI API: STUDI TENTANG HAMBATAN PELAKSANAAN PERAN - Tengku Romi Marnelly (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2018)
One of susceptible area that occurs the conflagration is Kampung Rawa Mekar Jaya, Subdistrict of Sungai Apit, Siak Regency, Province of Riau where a big part of its area possesses peat moss. The conflagration can be caused some factors among others dry season, canal making in the peat moss soil and the deliberateness of human in speeding up the plantation open. For saving and preventing and coping with the environment and the conflagration needs to have the good environment proces and it certainly needs to get the support and the role and the society. In the village, there is an institution that focuses on the environment process, the pure from the society self-support is namely The Institution of The Caring Society of The Fire that has duty on the activity of the prevention, the extinguishing and the handling of postconflagration of the forest and the land. The research has goal to know the obstacle or the hindrance for the staff of The Institution of The Caring Society of The Fire in implementing the role. The research method that is used is descriptive qualitative in sampling in census namely as many 23 people. The data is obtained through the observation, the direct interview by using the questioner. Based on the research result, The obstacle of staff of the Caring Society of The Fire in implementing the role known from the work environment, the society environment, the nature environment and the lack of the support especially from the side of the government and the private.